The predictive effect of relative intuition on social entrepreneurship orientation: How do exploratory and exploitative learning and personal identity interact? - Xiaobao, Peng; Hongyu, Chen; Horsey, Emmanuel Mensah (Acta psychologica, 2023)
This study complements the stream of psychology studies on the effects of an individual's intuition on strategic decisions and how it shapes behavioral tendencies by extending how these effects evolve social entrepreneurship orientation in social entrepreneurship. Theoretically, we establish the nexus between relative intuition and social entrepreneurship orientation as well as the moderating roles of exploratory and exploitative learning and personal identity. Empirical validation of these nexuses was based on a cross-section of 276 certified social enterprises in China. The findings indicate that social entrepreneurs' relative intuition has a positive association with social entrepreneurship orientation. Exploratory and exploitative learning positively mediate the nexus between relative intuition and social entrepreneurship orientation. In addition, personal identity positively moderates the effects of exploratory and exploitative learning on social entrepreneurship orientation. Subsequently, we found that the link between relative intuition and social entrepreneurship orientation strengthens as the social entrepreneurs' personal identity increases. In this light, we identify relative intuition as the foundation of exploratory and exploratory learning for the development of social entrepreneurship orientation. Similarly, we shed light on how personal identity positively facilitates the roles of these factors by arousing dedication to the processes/stages of the pursuit of social entrepreneurship orientation goal attainment.